Qualification and quantification of huperzine a from Huperia serrata in Da Lat, Lam Dong province - Ngọc, Vũ Thị; Hạnh, Phạm Thị; Anh, Lê Thị Lan; Đạt, Nguyễn Tiến; Thủy, Lê Thị Bích (Vietnam Journal of Biotechnology, 2016)
Huperzine A, an alkaloid, was originally isolated from Huperzia serrata. This compound potentially enhances the memory in animal, hence, it has been approved as a drug for the clinical treatment of Alzheimer’s disease, a major disease affecting the elderly population throughout the world. Because Huperzine A is an acetylcholinesterase inhibitor, the presentation of Huperzine A in brain inhibited acetylcholinesterase activity, thus, leading to the increase in concentration of acetylcoline. In Vietnam, H. serrata distributed in Sapa (Lao Cai) and Da Lat (Lam Dong), this species provide valuable pharmaceutical materials to the treatment for Alzheimer’s diseases. In this research, we evaluated the availability of Huperzine A in Huperzia serrata, which was collected from Da Lat (Lam Dong) in two seasons: Spring and Autunm. Thin layer chromatography (TLC) method was used to preliminary qualitative analysis. High performance liquid chromatography (HPLC) method were used for determining Huperzine A content in samples. In the result, Huperzine A is almost existed in leaves of Da Lat Huperzia serrata and equivalent levels of Chinese Huperzia serrata. The Content of Huperzine A was different between two collection samples in Spring and Autumn, by analyze HPLC data, the samples was harvested in Autumn contents 92.5 µg.g-1dry sample and the spring is 75.4 µg.g-1 dry sample. Therefore, the content of Huperzine A in Huperzia serrata’s leaves sample is harvested in the fall compared with samples collected in the spring is higher 17.1 µg.g-1dry samples.